ON A NEW MONOGENETIC TREMATODE, DOGIELIUS GUSSEVI N. SP. FROM A FRESHWATER FISH, RITA RITA (HAM.) - SINGH, HRDAYA SHANKFR; JAIN, AMITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
In the present paper, a new monogenetic trematode, Dogielius gusseyi n. Sp. collected from the gill filaments of a freshwater fish, Rita rita (Ham.) obtained at Meerut is described here with The new species differs from previously described three species in the number of head organ. by the presence of wings and accessory piece on the anchors, in having elongated cirrus and in the shape of copulatory complex.